Mrs. jeffries speaks her mind eaudiobook - Brightwell, Emily (Mrs. Jeffries, 2019)
The eccentric Olive Kettering swore someone was trying to harm her. Too bad no one listened, though plenty wanted her dead. When Olive is shot and killed, Mrs. Jeffries has no problem speaking her mind to see justice served.